Metodologiczne problemy w badaniach pokoleń. Wybrane zagadnienia = Methodological Problems in the Study of Generations - Zielińska, Maria; Szaban, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main goal of this article is to present basic ontological and theoretical difficulties and methodological problems occurring in the study of generations based on specific examples of empirical research conducted in Poland. The attempt was made to determine empirically so called empirical generation from longitudinal studies.
Keywords: pokolenie; badania; metodologia